STRATEGI KOMUNIKASI BISNIS DI ERA DIGITAL - Hendri Kremer (STKIP PGRI Sidoarjo, 2022)
Currently, business in Indonesia is growing rapidly along with technological developments. lots of new businesses have sprung up, whether it's business in the culinary sector, business in the service sector, or business in the transportation sector. Business development in Indonesia is also influenced by the industrial revolution 4.0, technology is developing rapidly and automation in all areas of life. Many workers do not know about business communication strategies in the digital era because of the lack of effective communication between workers, the lack of utilization of technology by the workforce so that knowledge of business communication strategies in the digital era is not optimal, the lack of use of the internet by employees, the lack of knowledge about communication between workers. SMKN 4 Batam Riau Archipelago